2020
DOI: 10.3389/fmicb.2020.584603
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Carbapenem-Resistant Acinetobacter baumannii Isolates Belonging to Major Endemic Clones in South America

Abstract: Carbapenem-resistant Acinetobacter baumannii (CRAB) are emerging worldwide. In South America, clinical isolates presenting such a phenotype usually do not belong to the globally distributed international clone 2 (IC2). The majority of these isolates are also resistant to multiple other antimicrobials and are often designated extremely drug-resistant (XDR). The aim of this study was to characterize the resistance mechanisms presented by 18 carbapenem-resistant A. baumannii isolates from five different Brazilian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 62 publications
5
36
0
Order By: Relevance
“…The prevalence of MDR/CRAb was very high. The results are in agreement with previous reports: most CRAb strains display resistance to at least one compound in three or more antimicrobial categories and are designated as MDR [ 6 , 7 ]. Resistance against imipenem was seen in 91.6% of XDR A. baumannii strains isolated from patients in three hospitals in southern Vietnam between 2012 and 2014 [ 17 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The prevalence of MDR/CRAb was very high. The results are in agreement with previous reports: most CRAb strains display resistance to at least one compound in three or more antimicrobial categories and are designated as MDR [ 6 , 7 ]. Resistance against imipenem was seen in 91.6% of XDR A. baumannii strains isolated from patients in three hospitals in southern Vietnam between 2012 and 2014 [ 17 ].…”
Section: Resultssupporting
confidence: 93%
“…Five strains appeared in three different clusters, and six strains were unique singletons. WGS showed a higher discriminatory power than conventional typing methods [ 6 ]. It allows a more precise trackback analysis of the strains, particularly when analyzing carbapenem-resistant A. baumannii isolates, which threaten the global healthcare system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight international clones were defined earlier [ 17 ], and the ninth was introduced recently [ 18 ]. The first three clones (IC1–IC3) are distributed worldwide, with IC1 and IC2 also known as global clones (GC), while the rest were sometimes defined as regional, or even endemic clones [ 13 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although many reports consider different clones or lineages of A. baumannii species to be associated with particular parts or regions of the world [ 13 , 20 , 21 , 22 ], the dramatically fast distribution of SARS-CoV-2 in 2020 has demonstrated that our knowledge regarding the spread of different pathogens is still limited.…”
Section: Introductionmentioning
confidence: 99%